Dynamics of Renal Histamine in Normal Rat Kidney and in Nephrosis Induced by Aminonucleoside of Puromycin - Abboud, Hanna E. (1982)
Histamine is known to have a profound effect on capillary permeability in nonrenal tissues and this effect is presumably mediated by cyclic (c)AMP. Because in our previous experiments we found that histamine stimulates cAMP accumulation in glomeruli (Torres, V. E., T. E. Northryn, R. M. Edwards, S. V. Shah, and T. P. Dousa. 1978. Modulation of cyclic nucleotides in isolated rat glomeruli. J. Clin. Invest.62: 1334.), we now explored whether this amine is formed in renal tissue, namely in glomeruli, and whether its renal metabolism is altered in experimental nephrosis induced by puromycin aminonucleoside (PA) in rats. In normal rats, histamine content was higher (Δ + 240%) in cortex than in medulla. In glomeruli isolated from renal cortex, histamine content was significantly higher (Δ + 260%) than in tubules. Incubation of isolated glomeruli with l-histidine resulted in a time-dependent increase of histamine content in glomeruli, but no change was found in tubules. The increase in glomerular histamine was blocked by the histidine decarboxylase inhibitor bromocresine. In rats with PA nephrosis induced by a single intraperitoneal injection of PA (15 mg/100 g body wt) urinary excretion of histamine was markedly increased (>Δ + 200%), but control rats did not differ from rats with PA nephrosis in urinary excretions of l-histidine and of creatinine. At the peak of proteinuria (day 9 after injection of PA) the plasma level of histamine was slightly elevated, and plasma histidine slightly decreased in animals that developed PA nephrosis. The content of histamine was markedly higher and the level of histidine was significantly lower in the renal cortex of PA-nephrotic rats as compared with controls; PA-nephrotic and control rats did not differ in the content of histidine and histamine in the liver. In addition, the content of histamine was higher in glomeruli isolated from PA-nephrotic rats; lesser difference was found in cortical tubules. The results further indicate that PA-nephrotic rats have higher content of histamine in the renal cortex, predominently in glomeruli with increased urinary histamine excretion. The elevated renal cortical histamine is not due to higher availability of histamine precursor l-histidine. Results thus show that glomeruli are a major site of intrarenal histamine synthesis and accumulation, and also suggest that abnormal renal metabolism of this amine in PA nephrosis may be related, as a cause or as a consequence, to the pathogenesis of this disease.